Stability Indicating RP-HPLC Method for Estimation of Fexofenadine Hydrochloride in Pharmaceutical Formulation - H. M. Nimje; Shital T. Nimje; R. J. Oswal; S. T. Bhamre (E-Journal of Chemistry)
A stability-indicating HPLC method was developed and validated for the quantitative determination of fexofenadine in tablet dosage forms. An isocratic seperation was achieved using a Zorbax, Eclipse XBD, C-8 Column having 150 x 4.6 mm i.d., 5 µm particle size column with flow rate of 1.2 ml/min and using UV detector to monitor the eluate at 210 nm. The mobile phase consist of phosphate buffer: acetonitrile: methanol (60:20:20; v/v/v) with pH 3.7 adjusted with o-phosphoric acid. The drug was subjected to oxidation, hydrolysis, photolysis and thermal degradation. Fexofenadine was found to degrate in acidic, basic and oxidation condition. Complete seperation of degraded product was achieved from parent compound. All degradation products in an overall analytical run time of approximately 60 min with the parent compound fexofenadine eluting at approximately 12.1 ±0.9 min. The method was linear over the concentration range of 1-100 µg/ml (r2= 0.9970) with limit of detection and quatification of 0.2 µg/ml and 0.6 µg/ml, respectively. The method has the requisite accuracy, selectivity, sencitivity, precision and robustness to assay fexofenadine in tablets. Degradation products resulting from stress studies did not interfere with the detection of fexofenadine and the assay is thus stability indicating.